Autour de Batouala de René Maran : réflexions sur quelques formulations racistes et antiracistes du mot « nègre » - Elsa Geneste (Nuevo mundo - Mundos Nuevos, 2010)
In this paper, we would explore the different public uses of the word “nègre” in the context of the reception of René Maran’s novel Batouala after the award of the Goncourt Prize(1921). As it was used both to attack and to defend him, the French Caribbean writer was often the victim of misplaced identity attributions. For his part, Maran chose to dedicate a part of his work on the “nègre(s)” to understand what racism is.